2012
DOI: 10.1002/mnfr.201200047
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene inhibits lymphocyte proliferation through mechanisms dependent on early cell activation

Abstract: Scope: Epidemiological evidence suggests that lycopene is potentially cardio-protective. Recruitment and activation of T cells in the arterial wall is a critical process during atherogenesis, but the effects of lycopene on T-cell response remain to be elucidated. We aimed to determine whether lycopene could modulate T-cell function and activity. Methods and results: Peripheral blood mononuclear cells from 16 healthy adults were cultured in the presence of lycopene-enriched liposomes (0-2.9 g lycopene/mL) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Overall, results suggest that lycopene can neutralise reactive oxygen species, as well as reduce the secretion of pro-inflammatory cytokines and metalloproteinases by macrophages ( 78 , 79 ) , inhibit smooth muscle cell proliferation ( 80 ) and decrease monocyte proliferation ( 81 ) . More recently, work in our group showed that low, physiological concentrations of lycopene can significantly inhibit mitogen-activated T lymphocyte activation by modulating mechanisms involved in early activation ( 82 ) . Lycopene significantly inhibited mitogen-activated lymphocyte proliferation by up to 40 % and also significantly inhibited the expression of an early marker of activation, CD69, as well as IL-2 secretion.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Overall, results suggest that lycopene can neutralise reactive oxygen species, as well as reduce the secretion of pro-inflammatory cytokines and metalloproteinases by macrophages ( 78 , 79 ) , inhibit smooth muscle cell proliferation ( 80 ) and decrease monocyte proliferation ( 81 ) . More recently, work in our group showed that low, physiological concentrations of lycopene can significantly inhibit mitogen-activated T lymphocyte activation by modulating mechanisms involved in early activation ( 82 ) . Lycopene significantly inhibited mitogen-activated lymphocyte proliferation by up to 40 % and also significantly inhibited the expression of an early marker of activation, CD69, as well as IL-2 secretion.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Endothelial cell proliferation is positively related to EndMT. 30 LYC notably inhibits the proliferation of human peripheral blood mononuclear cells 31 and SKOV3 cells (a human ovarian adenocarcinoma cell line). 32 Data from the present study show that LYC inhibits the hypoxia‐induced proliferation of HCVECs.…”
Section: Discussionmentioning
confidence: 99%
“…As a highly effective antioxidant, lycopene can decrease the risk of disease by neutralizing reactive oxy-gen species (ROS) and reducing oxidative damage of some biomolecules (DNA, proteins, and lipids) [44,45]. In addition, lycopene has also acted through other mechanisms, including anti-inflammation [40], autophagy [46,47], apoptosis [48,49], proliferation [50,51], and pyroptosis [52].…”
Section: Biological Functions Of Lycopenementioning
confidence: 99%